Glycosidases from the culture medium of Physarum polycephalum. - Kilpatrick, D C (1977)
Eight exo-glycosidase activities were detected in the axenic culture medium of the myxomycete, Physarum polycephalum. The secretion of each enzyme examined followed the growth curve and continued during the stationary phase after the cessation of growth. Two or more forms of each enzyme were detected after electrophoretic separation. The beta-N-acetyl-D-hexosaminidase activity was readily separated into its two electrophoretic forms, X and Y, which were purified 145- and 306-fold respectively. These beta-N-acetyl-D-hexosaminidases had several similar characteristics. Evidence is presented that the major electrophoretic form of alpha-D-galactosidase is heterogeneous. The possible functions of extracellular glycosidases in teir occurrence and properties.